(untitled) (Interdisciplinary Studies Journal, 2024)
This article aims to examine the mechanisms for trading carbon credits in territories traditionally occupied in Portel, a municipality located in the Marajó mesoregion, State of Pará, identifying its controversies and ruptures based on the relationship with traditional local communities. As a methodology, indirect research techniques were used based on a documentary survey with the Public Ministry of the State of Pará (MPPA), Public Defender’s Office of the State of Pará (DPA) and information present on the virtual platform of the company Verra, the largest certifier of carbon credits in the world. The results show that carbon projects have been established in Portel for at least 15 years, covering an area of ​​714,085 hectares, focusing on forests located on non-designated public lands and located in state settlement projects. The research shows that Portel’s carbon projects are led by foreign capital, totaling 115 million dollars in potential sales values ​​for carbon credits. Such negotiations took place without transparency and without knowledge of local communities, characteristic of plunder and expropriation, explained by philosopher Nancy Fraser as the confiscation of human capabilities and natural resources to reallocate them to the circuits of expansion and accumulation of capital.